Inference-based User’s Recommendation in E-learning Systems - Elouahby, Youssef; Elouahbi, Rachid (Transactions on Engineering and Computing Sciences, 2017)
This paper proposes a technique of user’s recommendation for E-learning systems, which makes it possible to identify the best qualified profiles in a given field, the method is based on artificial intelligence in order to make connection between the knowledge expressed explicitly on a learner profile and a special need of another learner, not necessarily expressed on that profile, but which can be deduced through mechanism of inference.